Research of the modernized intake system of the gasoline engine - Mahats, M. I.; Hoshko, Z. O.; Vahula, Y. I.; Uzhva, A. V.; Магац, М. І.; Гошко, З. О.; Вагула, Ю. И.; Ужва, А. В. (Харківський національний автомобільно-дорожній університет, 2021)
Problem. In recent years, Ukraine has seen a sharp decline in ambient temperature, especially in the winter. Accordingly, this has a negative impact on the performance of car engines (difficult to start and prolonged warm-up), as the lion's share of private sector cars are parked in open areas and are subject to sudden temperature and humidity changes. Therefore, to partially solve this problem, our attention was focused on the air lines of the intake system of the gasoline engine, as this system is easily accessible and does not require significant design changes for its modernization. Goal. The purpose of the work is to ensure the ease of starting the gasoline engine and reduce the time to warm up. Methodology. Operation of the car in the conditions of the lowered temperatures, essentially promotes deterioration of its fuel economy. The basis of such a negative process of fuel consumption is incomplete combustion of the working mixture. And this is the deterioration of spraying and evaporation of fuel and increasing the duration of engine warm-up. At such low ambient temperatures, the effective operation of the car in a garage depends significantly on the method of its preparation (which should at a minimum cost of fuel and energy resources to ensure rapid and reliable engine start and accelerated warm-up). We decided to obtain thermal energy to heat the inlet air at no additional cost. This is the installation of a gasoline engine with a spark ignition of the incandescent coil in the intake air line, which will receive power from the battery. Such modernization of the system does not require major design changes and significant financial investments Unresolved issues remain to assess the effectiveness of the process of heating the air entering the combustion chamber of the engine to create a working mixture. It should be noted that the optimal heating of the engines is most appropriate to carry out (ie heating the coolant and oil in the engine lubrication system) not to the temperature of the operating thermal mode, but to the temperature that ensures its reliable start. Results. The scheme of connection of a heater of intake air in an onboard electric network of the car is presented. The results of the heat balance of the studied gasoline engine (using cold and heated air flow) during its heating are obtained. The optimum temperature of the warmed-up engine at which further economical operation of the car is possible is established. Originality. This spiral heater was first used to heat the intake air charge during the start-up and warm-up of a gasoline engine. Practical value. The developed heating equipment can be used for both gasoline and diesel internal combustion engines. It should be switched on only during engine start-up and warm-up.
Дослідження модернізованої впускної системи бензинового двигуна
Keywords: glowing filament; intake system; starting characteristics; engine warm-up time; fuel consumption; спіраль розжарювання; впускна система; пускові характеристики; час прогріву двигуна; витрата палива; 629.341; 10.30977/AT.2019-8342.2021.49.0.08